Pre-Exercise Caffeine Enhances Repeated Sprint Performance and Alters Physiological and Perceptual Responses with Effects Lasting up to 3.5 h - Mizuki Nishikawa; Manabu Shibasaki; Naoto Fujii (Medicine & Science in Sports & Exercise, 2026)
Introduction: Caffeine is well recognized to acutely enhance repeated sprint performance during intermittent exercise involving brief, repeated efforts. However, it remains unclear whether a single pre-exercise dose improves repeated sprint performance, and whether it alters noradrenergic, cardiorespiratory, and perceptual responses over several hours. Methods: 12 healthy young adults (4 females) completed two randomized, double-blind trials ingesting caffeine (5.5 mg·kg⁻¹) or placebo. Approximately 60 min after ingestion, participants performed three repeated sprint sets over a 3.5 h protocol. Each set consisted of 5 min of moderate-intensity cycling followed by 6 × 5 s sprints. Plasma samples were collected for caffeine and noradrenaline concentration analysis. Ratings of perceived exertion (RPE), leg muscle pain, respiratory variables, and heart rate were recorded. Middle cerebral artery mean blood velocity (MCA V mean ), an index of cerebral blood flow, was measured using transcranial Doppler, and carotid artery blood flow was assessed using ultrasound. Results: Caffeine increased mean sprint power across repeated sprint sets compared with placebo ( P < 0.05), with modest but consistent effects sustained up to 3.5 h post-ingestion (0.5-2.4%). Peak power was also enhanced in the second and third sets, with increases of up to 3.7% ( P < 0.05). These effects were accompanied by higher plasma noradrenaline concentrations ( P < 0.05) and lower RPE and leg muscle pain ( P < 0.05). Caffeine also reduced partial pressure of end-tidal CO 2 and MCA V mean , and increased heart rate ( P < 0.05). Conclusions: A single pre-exercise dose of caffeine (5.5 mg·kg⁻¹) sustains ergogenic effects across multiple repeated sprint bouts over 3.5 h post-ingestion. These improvements were observed alongside increased noradrenergic activity, reduced perceptual strain, and concomitant cardiorespiratory responses.